State policy to support manufacturing enterprises in foreign countries within the framework of targeted programs - Akbar Anvarovich Khakimov (Genius Journals, 2022)
The content and directions of state support for industrial enterprises in developed countries within the framework of targeted programs are scientifically studied in the article
Keywords: national economy; industry; industrial policy; investments